Transforming pipelines into digital platforms: An illustrative case study transforming a traditional pipeline business model in the standardization industry into a digital platform - Davis Adedayo Eisape (Journal of Open Innovation: Technology, Market, and Complexity, 2022)
For many, digital transformation is the new normal. However, in particular, pipeline businesses in traditional industries, such as standard-setting organizations (SSOs), are reluctant to radically rethink their business models, as they have often successfully prevailed for decades. The literature shows that there is a great deal of theory to be found on digital transformation, but a practical and, at the same time, scientific approach is yet missing. Following the design science framework, this paper introduces a two-step approach to transform a pipeline business model into a digital standardization platform. This is achieved by mapping the incumbent pipeline business mode146l and its ecosystem with the Platform Business Model Canvas introduced by Eisape. The representation of the current ecosystem is then digitally transformed according to the three key transformation points introduced by Alstyne et al., shifting the current ecosystem into the digital realm. The illustrative case study on DIN e.V. (the German SSOs) demonstrates the new methodology and its suitability for real applications. The result is a platform business model for a digital standardization platform, which, compared via an index to the traditional business model, has the potential to disrupt the entire standardization industry.
Keywords: 650; case study; digital transformation; DIN e.V.; ecosystem; platform business model canvas; standardization industry